Między etyką, estetyką i skutecznością komunikacyjną: idiostyl wczesnych książek Oriany Fallaci = Between ethics, aesthetics and effectiveness of communication: idiostyle of the early writings by Oriana Fallaci - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sharp style of Fallaci`s late writings is well known and discussed, but few research- ers deal with her titles from the late 50s and 60s. Especially in Poland, because most of her books from that period have not been translated into our language. It is therefore worthwhile to have a look at the young journalist`s ways to formulate thoughts in order to find the determinants of the idiostyle of her earlier texts.
Keywords: idiostyl; hiperbolizacja; powtórzenia; subiektywność; Fallaci, Oriana (1929-2006); idiostyle; hyperbolisation; repetition; subjectivity